Hydroxymethylglutaryl coA reductase (NADPH) in the latex of Hevea brasiliensis - Sipat, Abdullah B. (Elsevier, 1982)
The activity of hydroxymethylglutaryl CoA reductase (NADPH) (EC 1.1.1.34) was studied in the latex of regularly tapped mature trees of Hevea brasiliensis. The reductase activity was found mainly (95% of the total activity) in the pellet fraction (40 000 g) of the centrifuged latex. The enzyme in this fraction had a specific requirement for NADPH as the cofactor and, while not obligatory for activity, was activated by dithiothreitol at the optimum concentration of 2 mM. The pH optimum was found to be 6.6-6.9 in 0.1 M phosphate buffer. Mevalonate and CoA (at 2 mM each) did not affect enzyme activity, while hydroxymethylglutarate (2 mM) was slightly inhibitory. p-Chloromercuribenzoate (1 mM) completely inhibited this enzyme. The reductase activity in the 40 000 g pellet was not easily solubilized either using Triton X-100 or by sonication. The apparent Km for the washed, membrane-bound enzyme (103 000 g pellet) was 56 μ M (RS-HMG-CoA). Magnesium-ATP (4 mM) inactivated the reductase but this effect was greatly diminished or was absent upon washing the 40 000 g pellet.